Rejouer l’imprévu ?Le remake documentaire en question - Camille Bui (Mise au Point)
This article examines the possibility of remake in the field of documentary, by studying a set of contemporary urban films born from a desire of remaking classical pieces of the direct cinema movement: Chronicle of a Summer (Rouch et Morin, 1961), September Five at Saint-Henri (Aquin, 1962) and Place de la République (Malle, 1974). The question “can a documentary be remade?” allows us to rethink the nature and the becoming of direct cinema, as aesthetical object, historical testimony and social experience.The re-activation of a filmic device renders visible the evolution of a society decades apart, as well as it puts in perspective two states of cinema. Documentary remake is thus also always a sequel. On the aesthetical level, this approach stands between imitation and recreation of forms: by repeating the gesture of innovative works of the 1960-1970s, the contemporary “remakes” exist at the risk of betraying the experimental logic of their ancestors.